(untitled) (Itinera, 2015)
In this paper I aim at discussing the following questions: is improvisation an intentional action? If it is an intentional action, in what sense is improvisation intentional? Can improvisation contribute to the understanding of intentional action? I will argue that improvisation is not a bizarre case of action or a weakened action, but an intentional action in the proper sense (provided with some specific properties). Moreover, improvisation exemplifies key features of intentional action as such.